Numerical study of double-chambered perforated caisson with a top cover based on SPH method - Tang, Xiaocheng; Liu, Huayu; Mei, Lili; Fu, Pengshuai; Song, Dongrui; Chen, Hongzhou (Frontiers in Marine Science, 2023)
The Smoothed Particle Hydrodynamics (SPH) method modified by Corrective Smoothed Particle Method (CSPM) and Riemann solution is employed to simulate the interaction between double-chambered perforated caissons and waves. The accuracy and applicability of the numerical method are verified by the theoretical values and experimental data through comparisons. The effects of the top cover height s, the width of the wave dissipation chamber B and the perforated rate μ on the wave surface η or wave pressure p of the caisson are numerically analysis. The results show that under the calculated wave conditions, the top cover height s and perforated rate μ are significant factors affecting the wave dissipation performance of the caisson, while the width of the wave dissipation chamber B has little effect on the wave surface η. In the meanwhile, with the increase of the top cover height s, the wave pressure p on the front perforated plate and the back wall at the static water level gradually decreases, and the wave pressure p on the back perforated plate first decreases and then increases. In addition, the modified SPH method is also used to explore the changes of the pressure field and the velocity field of water particles, tracing the instantaneous velocity of water particles at different positions at different time, and describe the motion state of water particles, which provides effective facilitates for investigating the interaction between double-chambered perforated caissons and waves.